The Influence of Work Motivation and Organizational Culture on Employee Performance at Bank BJB Indramayu Branch Office - Aditya Arga Pradipta; Figna Dinanda Atriasti (Universitas KH. Abdul Chalim Mojokerto, 2026)
This study aims to analyze the effect of work motivation and organizational culture on employee performance at Bank BJB Indramayu Branch Office. The background of this research is based on a decrease in company profits by 58.59% in 2024 which indicates internal problems, especially in terms of employee motivation and work culture. The method used is a quantitative approach with a population of 250 employees and a sample of 155 employees. The research instrument was tested for validity and reliability, and all data has met the classical assumption test (normality, multicollinearity, and heteroscedasticity). The results showed that work motivation and organizational culture had a positive and significant effect both partially and simultaneously on employee performance. The R Square value of 0.745 indicates that 74.5% of the variation in employee performance can be explained by these two variables. This study concludes that increasing work motivation and positive organizational culture are very important in improving employee performance, and need to be the focus of management to face increasingly competitive business challenges.